1948
DOI: 10.2527/jas1948.71110x
|View full text |Cite
|
Sign up to set email alerts
|

The Apparent Digestibility of Prairie Hay of Variable Protein Content, with Some Observations of Fecal Nitrogen Excretion by Steers in Relation to Their Dry Matter Intake

Abstract: Materials and MethodsComplete botanical descriptions and the official grades of the various lots of prairie hay used in these experiments were not available. The hay was produced in the local area. It was composed largely of Little and Big Bluestem, with smaller amounts of less common grasses and some weeds. The different lots of hay varied in quality as would be expected of hay cut under favorable and unfavorable conditions in different seasons and in different years. The cottonseed meal which was fed as a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…(Hobbs et al, 1945). Feeding cottonseed meal (206 g to 1252 g) increased dry matter intake of prairie hay from 3.56 kg to approximately 4 kg (Gallup and Briggs, 1948). McCollum and Galyean (1985b) also noted an increase in intake of prairie hay from 1.69%…”
Section: Supplementation Of Grazing Cattlementioning
confidence: 89%
See 2 more Smart Citations
“…(Hobbs et al, 1945). Feeding cottonseed meal (206 g to 1252 g) increased dry matter intake of prairie hay from 3.56 kg to approximately 4 kg (Gallup and Briggs, 1948). McCollum and Galyean (1985b) also noted an increase in intake of prairie hay from 1.69%…”
Section: Supplementation Of Grazing Cattlementioning
confidence: 89%
“…Decreased forage N may limit the fermentative ability of cellulolytic bacteria in the rumen (Burroughs and Gerlaugh, 1949;Burroughs et al, 1949a;NRC, 1984;Horn and McCollum, 1987). Gallup and Briggs (1948) observed that as the protein content of the prairie hay decreased from 6% to approximately 3%, TDN content of the hay decreased from 56 to 41%. In addition, crude fiber digestibility decreased from 69 to 56% and apparent protein digestibility decreased from 41% to zero.…”
Section: Native Grass As a Forage Resourcementioning
confidence: 96%
See 1 more Smart Citation
“…Protein supplementation of low quality forages has been shown to increase digestibility (Gallup and Briggs, 1948) and voluntary intake (Elliott, 1967 Supplementing forages with cereal grains is often the most efficacious method of increasing the total intake of digestible energy. Protein supplementation of low quality forages has been shown to increase digestibility (Gallup and Briggs, 1948) and voluntary intake (Elliott, 1967 Supplementing forages with cereal grains is often the most efficacious method of increasing the total intake of digestible energy.…”
Section: Introductionmentioning
confidence: 99%
“…Good agreement losses. Several studies have shown positive relation-has been observed between estimates of undigested ships between faecal nitrogen excretion and the in-dietary nitrogen determined by direct chemical take of dry matter (Gallup & Briggs, 1948; Hutchin-analysis and by the conventional extrapolation proson, 1958), organic matter (Lancaster, 1949), nitro-cedure. It has also been shown that over 70 % of the gen (Raymond, 1948) and indigestible dry matter bacterial-I-endogenous debris nitrogen is incor- (Hutchinson & Morris, 1936).…”
Section: Introductionmentioning
confidence: 99%